Analysis of the Effectiveness of the CEKAS Program as a Promotive Preventive Service System for Non-Communicable Disease Control in Accordance with Minimum Service Standard - Nauli, Humaira Anggie; Yahya, Frida Laila; Syari, Wirda; Anggraini, Sevrima; Alfariyadi, Adwina Salsabila (Universitas Ibn Khaldun Bogor, 2025)
Non-communicable diseases (NCDs) have become a serious threat to public health worldwide, including in Indonesia. Puskesmas is a primary health care facility that plays an important role in the prevention and control of NCDs. The CEKAS (Cek Kesehatan Masyarakat - Community Health Check) Program is a NCD prevention initiative at the Puskesmas of Cianjur District. This article aims to analyze the effectiveness of the CEKAS Program in providing promotive preventive services for NCD control in Cianjur District based on program evaluation and its impact on the local community. This study used observational methods and secondary data analysis from Puskesmas reports related to the CEKAS Program. The results showed that the CEKAS Program played an effective role in reducing the incidence of NCDs in Cianjur Regency through prevention efforts and community education. With early detection and health education provided by the program, the community can take preventive measures to prevent non-communicable diseases and adopt a healthy lifestyle. However, there are still some challenges in the implementation of CEKAS, namely low public awareness, limited resources, lack of interdisciplinary cooperation, and non-comprehensive handling of examination results.